Regime Support and Gender Quotas in Autocracies - KILAVUZ, MUHAMMET TAHİR (My University, 2023)
Gender quotas are increasingly being adopted by autocrats in part to legitimize their rule. Yet, even in autocracies, these quotas increase women\"s political representation. It thus stands to reason that public support for gender quotas in autocracies might be shaped by this trade-off between advancing women\"s rights and granting the regime legitimacy. All else equal, regime opponents should be less supportive of gender quotas in autocracies, wary of legitimizing the regime. We uncover evidence of this proposition in an analysis of region-wide Arab Barometer surveys and a survey experiment in Algeria. We also find that evaluations of this trade-off are conditioned by other demographics, with women, gender egalitarians, and Islamists remaining more consistent in their support for/opposition to gender quotas regardless of regime gains. Overall, our findings suggest that gender quotas in autocracies are viewed through a political lens, creating a potential backlash toward women\"s empowerment.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Genel Sosyoloji ve Metedoloji; Bilim, Teknoloji ve Toplum; Social Sciences and Humanities; Sociology; General Sociology and Methodology; Science, Technology and Society; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; SOSYOLOJİ; SİYASET BİLİMİ; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; SOCIOLOGY; POLITICAL SCIENCE; Sosyoloji ve Siyaset Bilimi; Sosyal Bilimler ve Beşeri Bilimler; Siyasi bilimler ve Uluslararası İlişkiler; Sociology and Political Science; Social Sciences & Humanities; Political Science and International Relations